Risk assessment of metabolic syndrome in adolescents using the triglyceride/high-density lipoprotein cholesterol ratio and the total cholesterol/high-density lipoprotein cholesterol ratio - Shou-Yu Chu; Ji-Hyun Jung; Mi-Jung Park; Shin-Hye Kim (Korean Society of Pediatric Endocrinology, 2019)
Purpose This study was conducted to investigate the distributions of the triglyceride (TG) to high-density lipoprotein-cholesterol (HDL-C) ratio and total cholesterol (TC) to HDL-C ratio, and to explore their usefulness as markers of metabolic syndrome (MetS) in Korean adolescents. Methods We obtained data for 2,721 adolescents (1,436 boys and 1,285 girls) aged 10-18 years who participated in the Korean National Health and Nutrition Examination Surveys from 2008 to 2010. International Diabetes Federation criteria were used to define MetS. Results There were no significant gender-related differences in TG/HDL-C or TC/HDL-C ratios. These lipid ratios showed significant associations with homeostatic model assessment for insulin resistance (HOMA-IR) and waist circumference. Areas under the receiver operating characteristic curve to identify MetS were 0.947 for TG/HDL-C and 0.924 for TC/HDL-C, which were higher than that of HOMA-IR (0.822). Optimal cutoff values (sensitivity, specificity) of TG/HDL-C and TC/HDL-C ratios for MetS prediction were 3.3 (85.7%, 89.9%), and 3.8 (92.9%, 82.8%), respectively. Odds ratio (OR; 95% confidence intervals [CIs]) for MetS in adolescents with TC/HDL-C ratio above the cutoff value was 14.8 (2.8-77.4), while that for TG/HDL-C ratio about the cutoff value was 30.6 (6.0-157.6). In adolescents who had both lipid ratios above the cutoff values, the OR (95% CI) for MetS was 36.2 (7.2-186.2). Conclusion TG/HDL-C and TC/HDL-C ratios are useful markers of metabolic syndrome with high predictive value in Korean adolescents.